Pendampingan Masyarakat Desa Pringgasela Timur dalam Proses Pembuatan Bibit Hortikultura - Moh. Fauzan Azima; M. Harja Efendi; Heri Murtawan; Leny Fitriah; Husnul Budiatman Dani (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
East Pringgasela Village is located in Pringgasela Sub-district, East Lombok Regency, NTB. About 27.5 hectares of land in this village is agricultural. Therefore, the potential to develop horticultural crops is huge. Horticulture is the cultivation of fruits, vegetables and ornamental plants. The purpose of this mentoring activity is to empower the community to be more independent and able to develop their own agricultural businesses. The implementation method used is the method of socialization and direct practice. The results of mentoring activities for the eastern Pringgasela village community in the process of making horticultural seeds have succeeded in increasing community interest and have succeeded in empowering the community as evidenced by the presence of 5 people who will try to make nurseries independently. So this mentoring activity is strongly supported by the surrounding community as evidenced by the great enthusiasm of the community in participating in this activity.